The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.gca.2015.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and chlorine isotopologue fractionation of chlorinated hydrocarbons during diffusion in water and low permeability sediments

Abstract: To identify reactive processes in diffusion dominated water-saturated systems using compound-specific isotope analysis (CSIA), the effect of the diffusive transport process on isotope ratios needs to be known. This study aims to quantify the magnitude of carbon and chlorine isotopologue fractionation of two chlorinated hydrocarbons (trichloroethene (TCE) and 1,2-dichloroethane (1,2-DCA)) during diffusion in the aqueous phase and to relate for the first time laboratory with field results. Diffusion coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 76 publications
(109 reference statements)
8
44
0
Order By: Relevance
“…23 However, the magnitude of the shifts of carbon isotope ratios is much larger (up to 23.9‰) mainly in clay cores 13-14, 14-10, and 15-13 ( Figures 3B−D) than what is expected due to diffusion only (∼2‰). 23 Earlier CSIA aquifer measurements performed by Vargas 32 showed that five and six years after contaminant injection isotope signatures had not changed significantly upgradient of multitlevel row 15 within the zone where clay cores were retrieved. This suggests minor degradation in the aquifer upgradient of multilevel row 15 within the first six years after the contaminants were released.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…23 However, the magnitude of the shifts of carbon isotope ratios is much larger (up to 23.9‰) mainly in clay cores 13-14, 14-10, and 15-13 ( Figures 3B−D) than what is expected due to diffusion only (∼2‰). 23 Earlier CSIA aquifer measurements performed by Vargas 32 showed that five and six years after contaminant injection isotope signatures had not changed significantly upgradient of multitlevel row 15 within the zone where clay cores were retrieved. This suggests minor degradation in the aquifer upgradient of multilevel row 15 within the first six years after the contaminants were released.…”
mentioning
confidence: 82%
“…Besides reactive processes, it was assumed that the diffusive transport process is also associated with an isotope effect. Isotope fractionation factors due to diffusion were defined according to Wanner et al 23 The calibration of the model revealed that degradation is nonuniformly distributed in the aquitard (stronger close to the aquifer−aquitard interface than with increasing depth), which will be discussed in more detail in the "Results and Discussion" section. To quantify the quality of the fit between measured and modeled concentration and isotope data, the root mean squared error was used (RMSE; see eq 5 in the SI).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Such information can be highly valuable in field situations. Non-destructive abiotic natural processes, such as sorption, volatilization or diffusion strongly affect concentrations of a contaminant, but generally do not cause significant isotopic fractionation [51][52][53][54][55][56][57] . Temporal or spatial shifts in isotope ratios, in contrast, are highly indicative of degradation and can, therefore, better monitor the success of remediation strategies at contaminated sites than mass balances alone 58 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Despite the increased recognition of the quantitative importance and of the macroscopic impact of small scale diffusive processes on large scale transport of organic contaminants, only a few experimental and modeling studies have attempted to quantify diffusive isotope fractionation for organic compounds. [11][12][13][14][15][16] The lack of data and mechanistic understanding of organic chemicals' diffusive isotope fractionation becomes apparent when compared with the advances in the related field of inorganic isotope geochemistry, in which numerous studies have been carried out to investigate diffusive isotope effects of major cations, anions and dissolved gases in both aqueous solutions [17][18][19][20][21][22][23][24][25][26][27][28][29] and non-aqueous systems. [30][31][32][33] In this work we focus on diffusive transport of perdeuterated and non-deuterated benzene and toluene.…”
Section: Introductionmentioning
confidence: 99%